Investigation into the Structural, Chemical and High Mechanical Reforms in B4C with Graphene Composite Material Substitution for Potential Shielding Frame Applications - Ibrahim M. Alarifi (Molecules, 2021)
In this work, boron carbide and graphene nanoparticle composite material (B4C–G) was investigated using an experimental approach. The composite material prepared with the two-step stir casting method showed significant hardness and high melting point attributes. Scanning electron microscopy (SEM), along with energy dispersive X-ray spectroscopy (EDS) analysis, indicated 83.65%, 17.32%, and 97.00% of boron carbide + 0% graphene nanoparticles chemical compositions for the C-atom, Al-atom, and B4C in the compound studied, respectively. The physical properties of all samples’ B4C–G like density and melting point were 2.4 g/cm3 density and 2450 °C, respectively, while the grain size of B4C–G was in the range of 0.8 ± 0.2 µm. XRD, FTIR, and Raman spectroscopic analysis was also performed to investigate the chemical compositions of the B4C–G composite. The molding press composite machine was a fabrication procedure that resulted in the formation of outstanding materials by utilizing the sintering process, including heating and pressing the materials. For mechanical properties, high fracture toughness and tensile strength of B4C–G composites were analyzed according to ASTM standard designs. The detailed analysis has shown that with 6% graphene content in B4C, the composite material portrays a high strength of 134 MPa and outstanding hardness properties. Based on these findings, it is suggested that the composite materials studied exhibit novel features suitable for use in the application of shielding frames.